2020
DOI: 10.1111/cch.12829
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parental stress from admission to discharge in the neonatal special care unit

Abstract: Background Exacerbated parental stress during a stay in the neonatal intensive care unit can negatively impact the development of the hospitalized infant, strain the dyadic relationship and put parents at risk for poor mental health. It is therefore important to identify risk factors of stress throughout the duration of a hospitalization. This longitudinal study aimed to investigate sources of stress for mothers and fathers who had a baby in the neonatal special care unit. Methods Parents of 57 singletons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…This can be further enhanced by communicating with parents regarding their child's progress, providing individualised information on their infant's condition, and ensuring that parents feel their voices are heard regarding decision‐making. This is in line with recent local research in the area, with a study by Hames et al 22 . finding that the provision of appropriate information at different stages of the neonatal journey can allay concerns and alter parental perceptions of treatment efficacy and understanding of their infant's condition.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This can be further enhanced by communicating with parents regarding their child's progress, providing individualised information on their infant's condition, and ensuring that parents feel their voices are heard regarding decision‐making. This is in line with recent local research in the area, with a study by Hames et al 22 . finding that the provision of appropriate information at different stages of the neonatal journey can allay concerns and alter parental perceptions of treatment efficacy and understanding of their infant's condition.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with recent local research in the area, with a study by Hames et al . 22 finding that the provision of appropriate information at different stages of the neonatal journey can allay concerns and alter parental perceptions of treatment efficacy and understanding of their infant's condition. Another consistent message from the present study is how encouraging parental participation in care and providing regular information not only addresses a desire for control amidst uncertainty, but may further assist in supporting independent parenting.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the three groups did not differ at a global level or on PCDI and DC subscales. These findings seem to confirm that the consequences of preterm birth are related to its severity, with a greater psychological burden in terms of stress for fathers of severely preterm infants, particularly in the first months following birth, as evidenced by Ionio et al [ 26 ] and Hames et al [ 24 ]. In addition, they strengthen the empirical observation that the biggest source of stress is represented by parental role alteration, confirming previous studies [ 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 79%
“…In this sense, one of the psychological dimensions experienced by parents after preterm birth, and that could be related to depressive symptomatology, is a high level of stress (i.e., often referred to as psychological distress, parental stress, parenting stress, etc.). Several studies have indeed found a moderate–high amount of stress experienced by preterm babies’ mothers and fathers during baby hospitalization and also after discharge [ 24 , 25 , 26 , 27 ]. A systematic review highlighted that significant sources of high stress in fathers in NICU are represented by alteration of the parental role (e.g., limited or denied access to infant’s care, impaired opportunities to establish emotional bonding), infant appearance (e.g., perception of the infant as fragile, less responsive, more irritable), characteristics of NICU environment (e.g., intensity of sights and sounds of the NICU), staff communication (e.g., unsatisfying access to regular information about infant’s health and care) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,11 However, there is limited empirical description of the workful actions that parents do to be present. Challenges related to parenting an infant following preterm birth are addressed widely in the qualitative literature, 4,[13][14][15] but there are unspoken assumptions that parents can overcome barriers to being physically present. The aim of this study was to describe and examine how mothers' work was coordinated by institutional processes when participating in Alberta FICare.…”
mentioning
confidence: 99%